A new "knowledge-based engineering" guideline - Luft, Thomas; Roth, Daniel; Binz, Hansgeorg; Wartzack, Sandro (DS 87-6 Proceedings of the 21st International Conference on Engineering Design (ICED17), Vol. 6: Design Information and Knowledge, 2017)
It is necessary to enable product developers to use specific engineering knowledge in an efficient and fast way during the product development process. However, existing procedures supporting the development of products are not strictly convenient to meet this challenge. This is the reason why already in the 1980 various research approaches in the area of knowledge-based engineering (KBE) have been developed. Nevertheless, there is still no uniform and universally applicable description for the industrial environment, with which a KBE application can be implemented and operated. Therefore, the aim is empowering designers to use design-related knowledge in CAD-systems as a central engineering workbench. The main research question in this paper is: How to formulate a universally applicable procedure to conduct KBE-projects with all relevant roles as well as necessary instructions and recommendations regarding specific KBE-methods and -tools? By answering this question, this contribution offers insights in general adapted definitions and perspectives, a procedure for the implementation of KBE-projects, a classification of knowledge-based engineering and a first exemplary solution.
Keywords: Computer Aided Design (CAD); Computational design methods; Design informatics; Knowledge management; Product modelling